Creating the Nazi marketplace : commerce and consumption in the Third Reich - Wiesen, S. Jonathan (Cambridge Univ. Press, 2011)
"When the Nazis came to power in 1933, they promised to build a vibrant consumer society. But they faced a dilemma. They recognized that consolidating support for the regime required providing Germans with the products they desired. At the same time, the Nazis worried about the degrading cultural effects of mass consumption and its association with "Jewish" interests. This book examines how both the state and private companies sought to overcome this predicament. Drawing on a wide range of sources - advertisements, exhibition programs, films, consumer research, and marketing publications - the book traces the ways National Socialists attempted to create their own distinctive world of buying and selling. At the same time, it shows how corporate leaders and everyday Germans navigated what S. Jonathan Wiesen calls "the Nazi marketplace." A groundbreaking work that combines cultural, intellectual, and business history, Creating the Nazi Marketplace offers an innovative interpretation of commerce and ideology in the Third Reich"--